Determination of Total Phenolic Content and Antioxidant Activity of Tepache Fermented Product as Probiotic Beverage - Rejeki, Desi S.; Firsty, Girly R.; Azizah, Nur (Jurnal Akademika Kimia, 2025)
Tepache is a fermented beverage from Mexico that is made from pineapple peel. It can improve the balance of good bacteria and reduce the risk of gastrointestinal disease. Pineapple peel contains vitamin C, phenolic compounds, and flavonoid compounds, which have antioxidant function. There have been many studies on making tepache from pineapple peel. However, there is limited research about organoleptic tests with several influencing factors, such as the type of sugar and fermentation time. The research aimed to determine tepache beverages' total phenolic content and antioxidant activity. Tepache beverages are made with pineapple peel, brown sugar, and water, and then fermented for 1, 3, and 5 days. Gallic acid is used as a standard to determine total phenolic content. The DPPH test was carried out to determine its antioxidant activity. The result of the total phenolic contents in tepache beverages for 1, 3, and 5 days of fermentation was 0.0278 mg GAE/g sample, 0.0307 mg GAE/g sample, and 0.0436 mg GAE/g sample—antioxidant activity expressed by IC50 value. IC50 values in tepache beverages for 1, 3, and 5 days of fermentation were 160.198 ppm, 150.639 ppm, and 142.713 ppm. Tepache beverages have low total phenolic content levels and low to medium antioxidant activity.